Rapid quantification of 21 antihypertensive and diuretic drugs in plasma by UPLC-MS/MS: Application to clinical and forensic cases - Boudin, Coralie; Faure, Amandine; Behouche, Alexandre; Ormezzano, Olivier; Eysseric-Guérin, Hélène; Stanke-Labesque, Françoise; Paysant, François; Scolan, Virginie; Willeman, Théo (Journal of pharmaceutical and biomedical analysis, 2025)
Systemic arterial hypertension, affecting more than 1 billion people worldwide, necessitates widespread use of antihypertensive and diuretic medications. However, the potential toxicity related to exposure of these medications is not always fully understood, potentially leading to underestimates of deaths related to cardiovascular drugs. Additionally, the growing interest in monitoring adherence to antihypertensive medications necessitates the development of specific analytical methods suitable for both clinical and forensic applications. In this study, we developed a novel, high-throughput quantitative method for the simultaneous analysis of 21 antihypertensive and diuretic drugs mainly in human plasma using liquid chromatography with tandem mass spectrometry. This method has several advantages, including minimal sample volume requirement, a one-step sample preparation using an Ostro® plate, and a chromatographic run time of 7 min. The method was successfully validated on 11 criteria following the European Medicines Agency’s guidances. The method was successfully applied to authentic samples from 62 clinical cases and 76 post-mortem cases, with two cases of severe intoxications more precisely described. The first case describes an attempted suicide by candesartan (2558 ng/mL in plasma) combined with celiprolol (18 ng/mL) and amlodipine (161 ng/mL). The second case is a diuretic-contaminated dietary supplement poisoning with plasma concentrations of 40 ng/mL for furosemide and 36 ng/mL for hydrochlorothiazide. The authors present a simple, fast, and sensitive quantification method for the analysis of 21 antihypertensive and diuretic drugs, with concentration values reported in both living subjects and post-mortem cases to aid in the often-challenging interpretation of cardiotropic drug concentrations. •An analytical method for the quantification of 21 antihypertensive and diuretic drugs.•A method suited for clinical and forensic analyses.•15 min from sample preparation to result.•Low LOQ (0.5 or 5 ng/mL) obtained with 50 µL sample.